Making a Punjabi Language Documentary Film in New Zealand for Punjabi and Non-Punjabi Audiences - Brown Pulu, Teena; Mukhtar Janjua, Asim (Faculty of Maori and Indigenous Development, Auckland University of Technology, 2020)
The second author interviewed three Punjabi Sikhs in South Auckland on camera in the Punjabi language, and two Punjabi Muslims in Lahore via an online video call where one participant responded in Punjabi and the other in the Urdu language. Their discussions were edited and subtitled in English for a thirteen minute documentary film screened at a migration research symposium and also released on the internet via Punjabi, Indian, and Pakistani multimedia outlets. Our paper speaks about the process of making a Punjabi language documentary in New Zealand for different audiences of university researchers and Punjabi communities. We also present the uncut interviews and the internet link to the film in Punjabi with English subtitles.